A critical impulse to e-governance in the Asia Pacific - SINGH, AMITA (Springer India, 2013)
This book presents a comparative study of the vision, ability and dynamism on the part of governments in selected Asian Pacific countries as they engage in the distribution of e-governance. Consequently, it creates a platform for mutual learning and offers a dispassionate evaluation of mega e-projects. It is an interdisciplinary study of information and communication technology within mainstream social science research and attempts to bridge the gap in empirical research between the nature of technology and the manner in which it is governed. The analysis shows that hegemonic and panoptic structures of surveillance and control may derail efforts to establish sustainable e-governance, while a liberal futuristic framework with open socio-technology networks on Big Data analytics, IPv6 and Cloud Computing may strengthen the trend towards democratizing institutions. Further, the book highlights the extraordinary energy being generated in the emerging new world through their use of the internet and suggests how governments could translate this into a new wealth of economic opportunities, social inclusion and equitable development, in addition to achieving the MDGs (Millenium Development Goals). Lastly, it emphasizes the importance of a visionary approach, which, wherever present, has been able to sustain e-governance by meaningfully linking the micro to the macro and heritage to the horizon.